Experimental Investigation of Papercrete Bricks - Neha Thakur, Sandeep Salhotra (International Journal of Advanced Science and Technology, 2020)
This article infers the results of an experimental investigation of papercrete bricks and Co-Fi bricks manufactured by utilizing waste papers and coconut fibres in varying proportions. Four mix proportions were prepared i.e. 1:5:1, 1:5:2, 1:5:3, 1:5:4 (Cement: Sand: Paper Pulp) for the production of papercrete bricks. In this context, mix proportion of optimum result is chosen and partial replacement of sand by coconut fibre at the rate 1%, 2%, 3%, 4% was adopted for making Co-Fi bricks. To arrive at some conclusion, different test such as compressive strength test, weight test, water absorption test, XRD test were preformed. To check whether the brick is economical or uneconomical in comparison with conventional brick, cost analysis was made and found that Co-Fi bricks had low cost. Results obtained from this study showed very high compressive strength by partial replacement of sand with the coconut fibre. Owing to presence of coconut fibre improves the toughness and ductility behaviour of bricks. Co-Fi bricks have high energy absorbing ability and hence high compressivestrength.